Enhancement the stability of power system using optimal location of FACTS devices - Ali Najim Abdullah; Ahmed Majeed Ghadhban; Hayder Salim Hameed; Husham Idan Hussein (Institute of Advanced Engineering and Science, 2020)
This paper proposes a steady-state of the Static Var Compensator (SVC) & Thyristor Controlled Series Capacitor (TCSC) set up for enhancing the damping overall performance and growing the integral clearing time (CCT) of a power network. The indispensable clearing time is carried out through increasing the time fault interval until the gadget loses stability. Increasing the CCT can be contribute to reliability of the safety gadget, decrease the protection machine ranking and cost. In order to attain most enhancement of machine stability via optimizing location, sizing and control modes of SVC and TCSC. Models and methodology for putting and designing shunt FACT’s units SVC (injected reactive strength Q) and series FACT’s devices TCSC (chose capacitive region) are examined in a 6-bus system. Performance factors are described to show validation of SVC and TCSC on extraordinary conditions. It is proven that the SVC is better than TCSC.